Positive Psychological Attributes and Entrepreneurial Intention and Action: The Moderating Role of Perceived Family Support - Baluku, Martin Mabunda; Kikooma, Julius Fred; Otto, Kathleen; König, Cornelius J.; Bajwa, Nida ul Habib (Frontiers in Psychology, 2020)
Recent research illustrates substantial gaps between entrepreneurial intentions and behavior. This is a challenge for entrepreneurship promotion interventions that have primarily focused on stimulating entrepreneurial intentions. However, extant literature suggests that implementation intentions enhance the likelihood of acting congruently to the behavioral intention. Furthermore, theory also suggests the condition effects of situations and the perceived control over them. We therefore hypothesized that implementation intentions mediate the relationship between entrepreneurial intention and action, while perceived family support moderates the movement from implementation intention to entrepreneurial action. Using two-wave survey data from a sample of students at an African university, we measured two psychological attributes (proactive personality and psychological capital) as important precursors of entrepreneurship and entrepreneurial intentions present before undertaking an innovations and entrepreneurship course. Implementation intentions regarding entrepreneurship, entrepreneurial actions, and perceived parental support for entrepreneurial activities were also measured two weeks after completion of the course. Our results demonstrate support for the proposed moderated double mediation model in which the effects of the two psychological attributes on entrepreneurial actions are explained via entrepreneurial intentions and implementation intentions. We further find moderation effects of perceived family support indicating that implementation intentions more likely predicted entrepreneurial actions in cases of higher family support.